Text and its categories in contrastive approach - Tatiana Kananowicz (Opera slavica, 2018)
In the article the author gives reasons for using the concept of the text category as a unit of comparison of the texts created within the same discourse but in different languages. The author describes the procedure of text categories' eliciting through the example of the text category of impersonality and its implementation in Russian and Polish scientific texts.